2013
DOI: 10.1089/vbz.2012.1166
|View full text |Cite
|
Sign up to set email alerts
|

Recent Circulation of West Nile Virus and Potentially Other Closely Related Flaviviruses in Southern France

Abstract: In recent years, the number of West Nile virus (WNV) cases reported in horses and humans has increased dramatically throughout the Mediterranean basin. Furthermore, the emergence of Usutu virus (USUV) in Austria in 2001, and its subsequent expansion to Hungary, Spain, Italy, Switzerland, the United Kingdom, and Germany, has given added cause for concern regarding the impact of the spread of flaviviruses on human and animal health in western Europe. Despite frequent detection of WNV and USUV cases in neighborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…and a type of West Nile Virus (a Flavivirus) were also detected in ticks, but could not be confirmed. Both agents are known to be transmitted by different species of soft ticks (Lawrie et al., 2004, Cutler, 2010) and WNV has been previously reported in the Camargue region (Balança et al., 2009, Vittecoq et al., 2013, Pradier et al., 2014). However, a previous study of Yellow-legged gulls on Carteau did not find evidence for the presence of Flavivirus antibodies in eggs, suggesting that WNV and other related viruses may not have circulated in gulls at that time (Arnal et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…and a type of West Nile Virus (a Flavivirus) were also detected in ticks, but could not be confirmed. Both agents are known to be transmitted by different species of soft ticks (Lawrie et al., 2004, Cutler, 2010) and WNV has been previously reported in the Camargue region (Balança et al., 2009, Vittecoq et al., 2013, Pradier et al., 2014). However, a previous study of Yellow-legged gulls on Carteau did not find evidence for the presence of Flavivirus antibodies in eggs, suggesting that WNV and other related viruses may not have circulated in gulls at that time (Arnal et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to WNV, it rarely causes severe neurological symptoms in humans, but virulent strains have caused considerable bird mortality, especially in blackbirds ( Turdus merula ) in central Europe, starting in Austria in 2001 [67,68]. USUV is known to circulate in Hungary, Switzerland, Italy, Spain, the Czech Republic and Germany [69,70,71,72,73,74,75], and USUV neutralizing antibodies were recently found in animals in France and Croatia [76,77]. …”
Section: Flavivirus Diversity In Europementioning
confidence: 99%
“…However, serological studies conducted from 2005–2007 in wild birds in Camargue showed that two juveniles sampled in 2006 were seropositive and that another seroconverted in 2007, thus revealing circulation of the virus in Camargue during this period [8]. In another investigation, conducted in this area during 2009, a high titer of WNV-neutralizing antibodies was found in a second year magpie ( Pica pica ), indicating its recent exposure to the virus [9]. Thus, despite evidence of the regular circulation of WNV in wild birds in Camargue, no clinical case has been reported in this area since 2004.…”
Section: Introductionmentioning
confidence: 99%